The morphological and biochemical effects of feeding Hooker’s pitcher with Formica fusca or Calliphora vicina Larvae - Wróbel, Jacek; Wróbel, Mariola; Przybylska, Urszula; Telesiński, Arkadiusz (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this study was to determine if feeding Hooker’s pitcher (Nepenthes × hookeriana) with blowfly larvae (Calliphora vicina Rob-Desvoidy) or ants (Formica fusca L.) affected the plant’s biometric and biochemical parameters. The research included measurements of length and width of the laminae and pitchers, and the total contents of the ash, assimilation pigments, polyphenols, and flavonoids. These parameters were measured 30 days after the last feeding. This study demonstrated that feeding the plants with blowfly larvae resulted in increases in the lengths and widths of both the laminae and pitchers. Moreover, the laminae had reduced carotenoid content after feeding with blowfly larvae and ants whereas the pitchers of Hooker’s pitcher had increased chlorophyll and carotenoid content after feeding with blowfly larvae. Feeding Hooker’s pitcher plants with blowfly larvae also resulted in a reduction of the total polyphenol content in the laminae whereas the total flavonoid content increased in both the laminae and pitchers of Hooker’s pitcher. Feeding Nepenthes × hookeriana with insects ensures that their nutritional needs are met and leads to pitchers with good physiological condition.